FACTORS THAT CAUSE SYNTAGMATIC DISPARITY TYPICAL OF SENTENCES (Scientific journal of the Fergana State University, 2024)
This article reflects on the formal and substantive structure of a sentence, the main factors that create a disparity of form and content inherent in sentences, in particular paradigmatic and syntagmatic disparity. Syntagmatic disparity is the presence of organized and separated commas, exclamations, inputs and inputs, exclamations in predicative sentence devices, the non-conformity of the amount of semantic units of the sentence content in such devices with formulaic – grammatical units, expressed through certain propositions, oborates, through certain words and grammatical forms in a simple sentence, complicating this simple sentence by content, redundancy inherent in simple sentences, often, the emergence of asemantic simple content, which can also be expressed in simple sentences in determinative and adverbial adjuncts, can be given in a complex form-in polypredicative devices, linguistic economy is a contradictory concept of linguistic redundancy, in which the formative-grammatical units of the semantic whole are less than its figurative-semantic units, while some units of the semantic construction of the sentence do not have a material image in the grammatical construction of the sentence are illuminated on the basis of examples from works of art.